Ella purātanara vacanagaḷu - Rājūra, Viraṇṇa,Śirūra, B. V.,Veṅkāreḍḍi, Madhu (Jagadguru Śrī Śivarātrīśvara Granthamāle)
bhāga 1. Kōlaśāntayyana vacanagaḷinda ārambhavāguva sampuṭa / sampādakaru, Vīraṇṇa Rājūra – bhāga 2. Goggavveyara vacanagaḷinda ārambhavāguva sampuṭa / sampādakaru, Bi. Vhi. Śirūra – bhāga 3. Basavaṇṇanavara vacanaḷinda ārambhavāguva sampuṭa / sampādakaru, Madhu Veṅkāreḍḍi Collection of ancient vachanas (devotional writings) from various Kannada saint poets
Kannada in kanares. Schr
Keywords: Epigrams; Kannada